The Effectiveness of English as a Science Medium Instruction in Higher Education - Meikardo Samuel Prayuda; Natalina Purba; Candra Ronitua Gultom (Postgraduate, University of Mataram, 2024)
This research presents a comprehensive analysis of English as a Medium of Instruction (EMI) in higher education, drawing insights from seven studies involving 150 students. The investigation delves into various factors such as academic proficiency, TOEFL scores, and gender distribution. Findings reveal a clustering of TOEFL scores around the midpoint of the range, suggesting a normal distribution. However, gender distribution exhibits significant deviations from normalcy. Despite these variations, detailed statistical analyses offer valuable insights into student performance within EMI programs. Moving beyond data analysis, a systematic review explores the impact and effective practices of EMI in higher education. It acknowledges the ongoing debate regarding EMI's influence on language proficiency and academic achievement. While some studies suggest positive outcomes, others highlight challenges and discrepancies, emphasizing the complexity of evaluating EMI's success. The review underscores the importance of examining diverse linguistic and non-linguistic factors and calls for further research to inform instructional strategies. Furthermore, the study identifies effective practices in EMI implementation, emphasizing instructional techniques, curriculum design, language support services, assessment procedures, faculty development, and reflective practice. These approaches aim to create inclusive learning environments conducive to language acquisition, subject matter learning, and student success. Additionally, the review proposes solutions to address challenges and promote inclusivity in EMI contexts, including cultural orientation programs, academic assistance, institutional regulations, social justice initiatives, intercultural competencies, and student-centered teaching approaches. This holistic approach seeks to enhance the long-term success and well-being of students within the EMI framework in higher education.